Ductile failure analysis of high strength steel in hot forming based on micromechanical damage model - Ying Liang; Liu Wenquan; Wang Dantong; Hu Ping (MATEC Web of Conferences, 2016)
The damage evolution of high strength steel at elevated temperature is investigated by using the Gurson-Tvergaard-Needleman (GTN) model. A hybrid method integrated thermal tensile test and numerical technique is employed to identify the damage parameters. The analysis results show that the damage parameters are different at different temperature as the variation of tested material microstructure. Furthermore, the calibrated damage parameters are implemented to simulate a bugling forming at elevated temperature. The experimental results show the availability of GTN damage model in analyzing sheet formability in hot forming.